(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This paper seeks to understand the self-expressed job identity and precarity of Korean filmmakers by examining how filmmakers replicate themselves in the film. The identity of a film industry worker is best shown by its character's reflective nature. Thus, it might be helpful to look at how Korean filmmakers see themselves while also looking at what they want to reflect in the outer world. The implication of this research method is to investigate identity through film representation. Ultimately, all Korean filmmakers are precarious. Their films are a reflection of the times. They are all eager to make a successful film and appreciate the importance of film in comparison to other forms of media. The greatest incentive for filmmakers to overcome the industry's precarity is to undertake creative work in order to follow their goals and craft. However, because artists tend to be self-centered, filmmakers secretly desire both honor and wealth but are reluctant to admit that they are also seeking wealth for the sake of others.